Access to antivenoms in the developing world: A multidisciplinary analysis. (November 2021) - Potet, Julien; Beran, David; Ray, Nicolas; Alcoba, Gabriel; Habib, Abdulrazaq Garba; Iliyasu, Garba; Waldmann, Benjamin; Ralph, Ravikar; Faiz, Mohammad Abul; Monteiro, Wuelton Marcelo; de Almeida Gonçalves Sachett, Jacqueline; di Fabio, Jose Luis; et al.
Abstract: Access to safe, effective, quality-assured antivenom products that are tailored to endemic venomous snake species is a crucial component of recent coordinated efforts to reduce the global burden of snakebite envenoming. Multiple access barriers may affect the journey of antivenoms from manufacturers to the bedsides of patients. Our review describes the antivenom ecosystem at different levels and identifies solutions to overcome these challenges. At the global level, there is insufficient manufacturing output to meet clinical needs, notably for antivenoms intended for use in regions with a scarcity of producers. At national level, variable funding and deficient regulation of certain antivenom markets can lead to the procurement of substandard antivenom. This is particularly true when producers fail to seek registration of their products in the countries where they should be used, or where weak assessment frameworks allow registration without local clinical evaluation. Out-of-pocket expenses by snakebite victims are often the main source of financing antivenoms, which results in the underuse or under-dosing of antivenoms, and a preference for low-cost products regardless of efficacy. In resource-constrained rural areas, where the majority of victims are bitten, supply of antivenom in peripheral health facilities is often unreliable. Misconceptions about treatment of snakebite envenoming are common, further reducing demand for antivenom and exacerbating delays in reaching facilities equipped for antivenom use. Multifaceted interventions are needed to improve antivenom access in resource-limited settings. Particular attention should be paid to the comprehensive list of actions proposed within the WHO Strategy for Prevention and Control of Snakebite Envenoming. Highlights: The global antivenom market is fragmented into multiple sub-markets of region-specific products, leaving many needs unmet. Weaknesses in national regulatory capacity and some manufacturing processes lead to procurement of substandard antivenoms. Prompt access to antivenom in rural settings is challenging due to lack of transportation. Scarcity of adequately resourced facilities with experienced staff to administer antivenom is another access barrier. Fully-financed regional antivenom stockpiles have the potential to significantly improve access.